Conceptualizing and Studying Characteristics, Units, and Fits of Persons and Environments: A Coherent Synthesis. Issue 3 (May 2022) - Kandler, Christian; Rauthmann, John F.
Based on a perspective on personality coherence as the extent to which personality-relevant characteristics are differentiated and integrated within a person in his or her environment, we propose a synthesis that builds on and harmonizes existing and partly conflicting theories, methodological approaches, and empirical findings. This understanding of personality coherence needs clear definitions of person and environment characteristics. We define traits as characteristics of the person, adaptations as characteristics of the person-in-contexts, and states as characteristics of the person-in-situations. Thus, our synthesis involves concepts of environments and person-environment units. Next, we provide testable criteria to differentiate characteristics of persons from characteristics of person-environment units and to identify dispositional traits for a narrow-sense perspective on personality coherence. We raise awareness of the importance of fit between (profiles of) person and environment characteristics for an understanding of the integrated uniqueness of persons in their environments. We outline implications of this broader perspective on personality coherence for personality development, self-regulation, social integration, well-being, and psychological interventions. Lastly, we conclude that the analysis of an individual's uniqueness and personality differences requires information about how well-defined, well-differentiated, well-integrated, and well-operationalized person(ality) variables are actually expressed in, or interact and transact with, the individual environment.